2013
DOI: 10.1038/onc.2013.161
|View full text |Cite
|
Sign up to set email alerts
|

LPLUNC1 suppresses IL-6-induced nasopharyngeal carcinoma cell proliferation via inhibiting the Stat3 activation

Abstract: Tumor-associated macrophage (TAM)-related chronic inflammation and interleukin-6 (IL-6) contribute to the progression of nasopharyngeal carcinoma (NPC). In this study, we characterized TAMs and IL-6 expression in 212 biopsied NPC and 119 non-tumor nasopharyngeal epithelium (NPE) tissues by tissue array. In comparison with that in the NPE tissues, more TAM infiltrates and a higher density of IL-6 expression were detected in NPC tissues, which were associated with the poor survival of NPC patients. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 52 publications
3
126
0
Order By: Relevance
“…A member of the bactericidal permeability-increasing protein and lipid-binding protein family, lplunc1 can be secreted by goblet cells and minor mucosal glands of the upper respiratory tract and oral cavity 13 . The protein inhibits lipopolysaccharide-induced interleukin 6 expression in npc cells and thus inhibits npc cell proliferation, induces npc cell arrest, and promotes npc cell apoptosis 12,13 . The correlation between elevated serum crp and a poor prognosis might reflect the prognostic value of tumour-produced interleukin 6, an inducer of crp production in the liver 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A member of the bactericidal permeability-increasing protein and lipid-binding protein family, lplunc1 can be secreted by goblet cells and minor mucosal glands of the upper respiratory tract and oral cavity 13 . The protein inhibits lipopolysaccharide-induced interleukin 6 expression in npc cells and thus inhibits npc cell proliferation, induces npc cell arrest, and promotes npc cell apoptosis 12,13 . The correlation between elevated serum crp and a poor prognosis might reflect the prognostic value of tumour-produced interleukin 6, an inducer of crp production in the liver 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously [30][31][32]. Cell lysates were separated by electrophoresis on 10 % sodium dodecyl sulfate (SDS) polyacrylamide gels, and the separated proteins were transferred to a polyvinylidene fluoride (PVDF) membrane (Millipore, Billerica, MA).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…progression and tumor metastasis. Liao et al (27) used NPC cell lines to detect that IL-6 promoted NPC cell proliferation in a dose-and time-dependent manner, and this was accompanied by increasing cyclin D1 and Bcl-2 expression, STAT-3 activation, and inhibition of Bax and p21 expression. Liu et al (28) observed that in certain macrophages of the tumor stroma of NPC tissue, IL-6-and TNF-α-dependent expression of tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase led to suppressed proliferation of T cells and impaired cytotoxic activity of CD8(+) T cells, thus facilitating immune escape.…”
Section: Discussionmentioning
confidence: 99%